Positive Discipline Impact on Students’ Self-Esteem in EFL Class in Tertiary Level - Nur Muthmainnah; Firmansyah Bayu Aji Manggala (Da'wa Faculty of Islamic State University Salatiga, 2024)
This research investigates the impact of positive discipline on students’ self-esteem and how it is implemented. A pre-experimental study followed by observation was applied in this research. This research was carried out at an English department of an Islamic University in Salatiga, Indonesia. An English class consisting of 33 students was chosen through cluster random sampling, and an English teacher was the sampler of this research. The pre-post-test was given to 33 students and adapted from Sorensen’s Self-Esteem Questionnaire. The observation was also employed to gather further information on how the teacher implemented positive discipline in the class. Positive Discipline practices in the class are reflected in how the teacher motivates students, praises students’ work, helps students’ problems, and involves students in arranging learning. Further, the mean score of students’ self-esteem questionnaire is decreasing, which means their self-esteem is increasing. Although they are classified in similar levels from 18.42 (severely low self-esteem) to 17.12 (severely low self-esteem), they have improved their self-esteem score. On the other hand, the result of the paired sample T-test represents the less significant positive discipline effect on self-esteem. The paired sample T-test value is 0.092, which is higher than 0.05. Thus, implementing positive discipline over extended periods in EFL learning might significantly affect students’ self-esteem.